Dziewiętnastowieczne listy gończe w badaniach nad urzędową polszczyzną wielkopolską - Pihan-Kijasowa, Alicja; Gucia, Dobrosława; Lubierska, Joanna (Slavia Occidentalis, 2015)
Arrest warrants published in the 19th century in Poznań have not been explored as the excellent material they are for historical and linguistic research. Published in the local newspapers and official journals: “Gazeta Południowo-Pruska”, “Gazeta Poznańska”, “Gazeta Wielkiego Księstwa Poznańskiego” and in “Publiczny Donosiciel. Dodatek do Dziennika Urzędowego Królewskiey Regencyi w Poznaniu”, they represent the bureaucratic variety of the 19th century Polish language used in Wielkopolska. On top of the linguistic forms typical of the 19th century, they represent considerable material illustrating two types of regional linguistic formations: old, traditional regionalisms and a layer of new regionalisms resulting from the influence of the German language9. What is more, arrest warrants offer interesting lexical material which allows to examine several areas of vocabulary with words related to garment as the best elaborate one.